Concentrated small extracellular vesicles from menstrual blood-derived stromal cells improve intrauterine adhesion, a pre-clinical study in a rat model. Issue 15 (13th April 2021) - Zhang, Siwen; Chang, Qiyuan; Li, Pingping; Tong, Xiaoyu; Feng, Yi; Hao, Xinyao; Zhang, Xudong; Yuan, Zhengwei; Tan, Jichun
Abstract : MenSCs-sEVs safely and effectively enhanced endometrial restoration, suggesting a promising non-cellular therapy for endometrial regeneration and a key role in MenSC-mediated IUA treatment. Abstract : We previously reported that transplantation of menstrual blood-derived stromal cells (MenSCs) significantly improved fertility restoration in intrauterine adhesion (IUA). However, it is difficult to obtain menstrual blood samples in some severe IUA patients who have amenorrhea or oligomenorrhea. Thus, a safe and effective stem cell replacement therapy is necessary to promote endometrial regeneration. Recent studies demonstrated that the effects of MenSCs are partly mediated in a paracrine manner via small extracellular vesicles (sEVs). To explore this possibility, we performed a pre-clinical study to investigate whether concentrated MenSC-derived sEVs (MenSCs-sEVs) are sufficient to repair IUA and the mechanisms underlying their action. Rat IUA models were established by mechanical injury, followed by the administration of MenSCs or MenSCs-sEVs through intrauterine transplantation. Consistent with the efficacy of MenSCs, MenSCs-sEVs effectively recovered the morphology, promoted regeneration of the glands and angiogenesis, and reversed endometrial fibrosis in the IUA uterus. The endometrial receptivity and pregnancy outcome significantly improved after repeated MenSCs-sEVs transplantations. In addition, all rats in the MenSCs-sEVs group had no hematological or biochemical abnormalities. Three-dimensional fluorescence imaging suggested that MenSCs tended to migrate through the bloodstream, whereas MenSCs-sEVs had a better localized therapeutic effect. Moreover, MenSCs and MenSCs-sEVs inhibited the TGFβ1/SMAD3 pathway in the IUA endometrium, while promoting the phosphorylation of SMAD1/5/8 and ERK 1/2 and upregulating the expression of BMP7. Thus, MenSCs-sEVs safely and effectively enhanced endometrial restoration, suggesting a promising non-cellular therapy for endometrial regeneration and a key role in MenSC-mediated IUA treatment.